Keputusan Mahkamah Konstitusi No. 67/Puu-Xi/2013 Tentang Uu No. 13 Tahun 2003 Tentang Ketenagakerjaan - Lendrawati Lendrawati; Rolend Santoso (Journal of Judicial Review, 2015)
Article 95 paragraph (4) Law Employment put workers wages in the position as preferred creditor. However, in Article 21 Law Taxation, the state has the right prioritize for tax debts on goods belonging to tax Insurer. This Article establishes the position of the State as a preferred creditor has the right prioritize over belongings Insurer Tax. Nine employees of PT.Pertamina applying conduct tests of Article 95 Paragraph 4 Law Employment to the Constitutional Court on and The Court granted the request of the applicant for the majority verdict that the judge that: Article 95 paragraph 4 of the Labor Law against the 1945 Constitution and has no binding legal force.Thesis research was conducted on the basic principle is to find out the considerations of law in Constitutional Court Decision and also to determine the legal measures that can be applied if the curator does not prioritize the payment of wages in bankruptcy.The methodology used in this research is normative juridical legal research using comparative law with the source data used in the form of secondary data obtained through library research. Basic legal considerations Judge of the Constitutional Court because that workers in accordance with Article 28D of the 1945 Constitution which the worker has the right to work and to receive compensation. It is also against the curators who are not running in accordance with the Constitutional Court's decision, it can bring a legal action by filing a lawsuit renvoi in accordance with Article 127 Law on Bankruptcy.